2014
DOI: 10.1002/mar.20746
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Focus Intensity and Evaluations of Retail Experiences

Abstract: Previous research indicates that consumers differ in their evaluation of and response to similar retail experiences. Reporting results from three studies, the current research proposes consumers’ regulatory focus intensity as one possible source of this variation. Study 1 examines how consumers’ regulatory focus intensity influences their in‐store behavioral intentions following good and bad shopping experiences. Study 2 illustrates how consumers’ regulatory focus intensity impacts their future loyalty intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Third, this study provides meaningful insights into how environmental factors interact with consumer characteristics. Although many studies have suggested that consumers' responses to the same store environment vary by consumer characteristics (e.g., Dijkstra, Pieterse, & Pruyn, ; Kwallek, Soon, & Lewis, ; Rompay, Vonk, & Fransen, ), very few studies have investigated consumer characteristics as the sources of the variations (Arnold, Reynolds, Jones, Tugut, & Gabler, ; Morrin &Chebat, ). To better understand the effects of store atmosphere, we examined individual differences in information processing styles as affective or cognitive processors.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this study provides meaningful insights into how environmental factors interact with consumer characteristics. Although many studies have suggested that consumers' responses to the same store environment vary by consumer characteristics (e.g., Dijkstra, Pieterse, & Pruyn, ; Kwallek, Soon, & Lewis, ; Rompay, Vonk, & Fransen, ), very few studies have investigated consumer characteristics as the sources of the variations (Arnold, Reynolds, Jones, Tugut, & Gabler, ; Morrin &Chebat, ). To better understand the effects of store atmosphere, we examined individual differences in information processing styles as affective or cognitive processors.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory focus has been found to play a key role in judgment and decision‐making (Arnold, Reynolds, Jones, Tugut, & Gabler, 2014; De Bock & Van Kenhove, 2010; Florack & Scarabis, 2006), especially in the context of consumer behavior (Hsu et al, 2017). Given that promotion‐focused individuals are motivated by ideals, growth, and advancement (Higgins, Roney, Crowe, & Hymes, 1994), they also show a propensity for risky decision‐making in pursuit of these positive results (Arnold et al, 2014; Crowe & Higgins, 1997). Uncertain situations in life such as expressing an opinion or providing feedback may risk disapproval (Podsakoff, MacKenzie, Paine, & Bachrach, 2000).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Since then, the topic has been studied by various researchers such as Pine and Gilmore (1998), Schmitt (1999), Addis and Holbrook (2001), Caru and Cova (2003), Lasalle and Britton (2003) and Brakus et al (2009). Brand experience occurs during various interactions that customers have with the brand and when consumers associate with the brand while searching for products, shopping for products or services and/or consuming products or services (Arnould et al , 2002; Brakus et al , 2008; Holbrook, 2000; Arnold et al , 2014). Pine and Gilmore (1998) investigated “staged experiences” in a retail environment and events.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%